Role of Dairy Cooperative Society in Empowering Women in Rural Odisha - Sasmita Dash, M.K Sarangi, Manoranjan Dash, Dhruti Sundar Sahoo, Kamalakanta Muduli (International Journal of Advanced Science and Technology, 2020)
In India the thrust of diary development program is to achieve socio-economic upliftment of rural women. In Odisha the Women milk producers cooperatives at the village level are operating with the aim of empowering rural women. A case study has been conducted among some selected women milk producers who are associated with siddheswari Women Milk producers co-operative society which is affiliated to Puri Milk Union (PUMUL) is operative in Puri district of Odisha. According to respondents  , change in  socio-economic situation of the women  is remarkable after joining the women milk producers cooperative society. However they face some constraints like sickness of dairy animals, high cost of cattle feed, non availability of hybrid cows in local market, lack of fund to expand farm and less profitability in dairy business.  The most important reason for joining cooperative society by these women  as observed in the study are employment at own house , flexibility in timing, increase in  family income, improvement in  social status, better education for children and  market access   and  economic independence.